Metabolic Profile in Neonatal Pig Hearts - Li, Pengsheng; Li, Fan; Tang, Ling; Zhang, Wenjing; Jin, Yan; Gu, Haiwei; Zhu, Wuqiang (Frontiers in Cardiovascular Medicine, 2021)
We evaluated the metabolic profile in pig hearts at postnatal day 1, 3, 7, and 28 (P1, P3, P7, and P28, respectively) using a targeted liquid chromatography tandem mass spectrometry assay. Our data showed that there is a clear separation of the detected metabolites in P1 vs. P28 hearts. Active anabolisms of nucleotide and proteins were observed in P1 hearts when cardiomyocytes retain high cell cycle activity. However, the active posttranslational protein modification, metabolic switch from glucose to fatty acids, and the reduced ratio of collagen to total protein were observed in P28 hearts when cardiomyocytes withdraw from cell cycle.